Mar de imagens: A relação estabelecida entre Eduardo de Martino, a Marinha Brasileira e as imagens produzidas pelo artista no final do século XIX - Lima, Bárbara Tikami de (Universidade do Vale do Rio dos Sinos, 2019)
This dissertation analyzes the relation between Eduardo de Martino (1838-1912), a neapolitan, and also a italian navy’s liutenant, who arrived in South America and resigned the military career to dedicate himself to the artistic race; the Brazilian Navy; and the images produced by this painter-sailor in the late nineteenth century. Therefore besides the historical contextualization of the period, we investigated the trajectory of the artist in what concerns his insertion in the artistic and military spheres; the appropriation of his screens and sketches by the Brazilian Navy and the manner wich his paintings had repercuted in his time’s press and how they were associated with the military institution.
Keywords: História da arte; História Militar; Eduardo de Martino; Marinha Brasileira; Imagens; History of art; Military History; Eduardo de Martino; Brasilian Navy; Images; ACCNPQ::Ciências Humanas::História